Personality, Preferences, Satisfaction, and Achievement in a Biostatistics Course: Traditional versus Flipped Classrooms in Nursing Education - Aina M. Yañez; Daniel Adrover-Roig; Miquel Bennasar-Veny (MDPI AG, 2023)
Background: In higher education, there is a lack of knowledge about how individual factors influence personal preferences for teaching methodology and academic outcomes in biostatistics among nursing students. This study sought to evaluate the associations between personality traits and preferences for the flipped classroom or traditional lessons, satisfaction, and achievement in a biostatistics course in nursing education. Methods: The cross-sectional study included data collection at two time points. During the 2018-2019 academic course, the flipped classroom approach was implemented into a biostatistics course of the nursing degree at the University of the Balearic Islands (Spain). Students responded to an online questionnaire including sociodemographic data, personality traits, locus of control, satisfaction, teaching quality, student involvement, and effort. After the final examination, students' achievements were collected. Results: A total of 137/161 (85.1%) students were included in the study. Most students preferred a flipped classroom to traditional lectures. Students who scored high in neuroticism preferred the traditional class (p < 0.001). Furthermore, personality was associated with satisfaction: high levels of responsibility and internal locus of control were significantly associated with higher satisfaction (p < 0.05). The percentage of students who did not pass the biostatistics exam was reduced by 50% with the flipped classroom methodology (33% vs. 15%; p < 0.001). Conclusions: A flipped classroom is adequate for the biostatistics course. Teachers should reconsider possible reservations about new teaching methods, which can be related to student personality.